A gazdasági szervezetek szerepe a közösségi fejlesztések finanszírozásában - László, Mária (Tér és Társadalom, 1998)
In the theoretical studies of economics, private enterprises in financing public services are considered either as additional resources to governmental expenses or as entities investing into human capital for improving their competitiveness. The environmental approach puts enterprises into the context of the system of social, economic and institutional relations that have a considerable impact on economic decision-making process. In this way, enterprises have an important part in social harmony and economic development. Since financial resources of local governments for the operation and development of public services are scarce, local enterprises are considered as potential partners of authorities in such activities. Collaboration between local actors should result a more efficient service system of a higher quality. Such projects reflects the transition process in the environment of the Hungarian local government system, such as structural and spatial changes in the economy, social and regional differentiation and conflicts that effected relations of the public and private sector as well. To manage such problems, regional development policies should consider not only public institutions and authorities but also private enterprises as actors of spatial development. For this purpose, decentralised and operational framework of territorial administration must be established. In the transition period, regional development projects were implemented by sovereign local governments having scarce financial resources. They received no significant support from large scale service companies (enjoying the status of monopoly) and were often exposed to the unfair business conduct of private contractors. Such conflicts should be eliminated through co-operation between the public and private sectors resting on reciprocity. The first steps towards broadening such "horizontal" relations must be the integration of interests and purposes of enterprises into local development strategies and defining the conditions of collaboration in formai contracts. In this way, development policies of the local government will be supported widely.